Strategi Peningkatan Kualitas Pendidikan di Kabupaten Tanggamus - Dini Pepilina (Journal on Education, 2022)
The article discusses the importance of education in national development, particularly in shaping the character and quality of qualified human resources. However, the quality of education in Indonesia, including in Kabupaten Tanggamus, is still a concern due to various challenges, such as inadequate facilities, low quality of educators, and low student interest. Therefore, this research aims to identify the factors that affect the quality of education in Kabupaten Tanggamus and evaluate the strategies implemented to improve it. The study uses a descriptive research design with qualitative and quantitative approaches, with a purposive sample of ten schools representing various educational levels. Data is collected through questionnaires for teachers and students and in-depth interviews with school principals and education departments. The data is analyzed using descriptive statistical techniques and qualitative analysis. The results of the study are expected to contribute to improving the quality of education in Kabupaten Tanggamus and serve as a reference for those interested in the field of education.